Macromorphology, Microstructure, Mechanical Properties, and Elemental Composition of Enamel and Dentine in the Eurasian Otter Lutra lutra - Yahya AlShukri; Ingrid N. Visser; Øystein Wiig; Carolina Loch (International Journal of Zoology)
Eurasian otters (Lutra lutra) are mammals found in waterways and coastal areas of Europe, parts of Asia, and northern Africa, where they inhabit aquatic environments with adequate food resources, primarily fish. This descriptive study aimed to investigate and describe the macromorphology, microstructure, mechanical properties, and elemental composition of teeth in two subadult Eurasian otters. A total of six teeth, comprised of two upper incisors, two canines, one premolar, and one molar tooth of two subadult Eurasian otters were analyzed. Teeth were measured, photographed, embedded in epoxy resin, sectioned, polished, and etched for scanning electron microscope (SEM) imaging, nanoindentation, and elemental composition analyses. The enamel of the Eurasian otter specimens analyzed was prismatic, ranging in thickness from 115 to 250 μm in incisors, 150–265 μm in canines, and 120–930 μm in postcanine teeth. The overall enamel microstructure was characterized by distinct transversely oriented undulating Hunter–Schreger bands, running from the enamel–dentine junction (EDJ) to the outer enamel surface, with bands of 5–8 prisms thick. The prisms were semicylindrical in shape with 4–6 μm diameter. Enamel tufts and lamellae were observed near the EDJ, which was straight with minimal scalloping. CaO and P2O5 were the main components in both enamel and dentine; other minor components such as Na2O, MgO, Cl, and SrO were also observed. The dental characteristics of Eurasian otters are similar to other carnivores and reflect their diet and phylogeny. Such comparative dental studies can contribute to our understanding of the biology, functional morphology of and evolution of otters and other closely related species.